Protein Synthesis by Platelets: Historical and New Perspectives - Weyrich, Andrew S. (2008)
In the late 1960’s numerous investigators independently demonstrated that platelets are capable of synthesizing proteins. Studies continued at a steady pace over the next 30 years and into the 21(st) century. Collectively, these investigations confirmed that platelets synthesize proteins and that the pattern of protein synthesis changes in response to cellular activation. More recent studies have characterized the mechanisms by which platelets synthesize proteins and have shown that protein synthesis alters the phenotype and functions of platelets. Here, we chronologically review our increased understanding of protein synthetic responses in platelets and discuss how the field may evolve over the next decade.